RETRACTED: Citizen safety and rights protection in emergencies: Legal insights - Arkhireyskaya Tatyana; Borisov Yan; Sokolova Anna; Sokolova Oksana (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001